2003
DOI: 10.1099/mic.0.26301-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification and study of a Candida albicans protein homologous to Saccharomyces cerevisiae Ssr1p, an internal cell-wall protein

Abstract: After screening of a Candida albicans genome database, the product of an ORF (IPF 3054) that has 62 % homology with Saccharomyces cerevisiae Ssr1p, an internal cell-wall protein, was identified and named CaSsr1p. The deduced amino acid sequence shows that CaSsr1p contains an N-terminal hydrophobic signal peptide, is rich in Ser and Thr amino acids and has a potential glycosylphosphatidylinositol-attachment signal. CaSsr1p is released following degradation of isolated cell walls by zymolyase (mainly a 1,3-b-glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0
2

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 54 publications
0
26
0
2
Order By: Relevance
“…In their analyses, they listed 115 putative GPI-CWP class proteins (see Table 1 in the work of Richard and Plaine [312]); 70 were common to all three reports, 6 were found in common between the analyses of de Groot et al (74) and Eisenhaber et al (92). The remaining proteins were unique to one of the studies: 24 proteins from the study of de Groot et al (74), 9 from the study of Eisenhaber et al (92), and 6 from the study of Garcerá et al (118). GPI anchors may target proteins to the membrane or the cell wall.…”
Section: Gpi-cwpsmentioning
confidence: 97%
See 2 more Smart Citations
“…In their analyses, they listed 115 putative GPI-CWP class proteins (see Table 1 in the work of Richard and Plaine [312]); 70 were common to all three reports, 6 were found in common between the analyses of de Groot et al (74) and Eisenhaber et al (92). The remaining proteins were unique to one of the studies: 24 proteins from the study of de Groot et al (74), 9 from the study of Eisenhaber et al (92), and 6 from the study of Garcerá et al (118). GPI anchors may target proteins to the membrane or the cell wall.…”
Section: Gpi-cwpsmentioning
confidence: 97%
“…Several studies have reported analyses of the C. albicans genome for proteins included in the GPI-CWP class (1,74,92,118,371). These proteins have been recently reviewed by Richard and Plaine (312), who focused on the three reports that used C. albicans genome assembly 19 (74,92,118).…”
Section: Gpi-cwpsmentioning
confidence: 99%
See 1 more Smart Citation
“…Four different lists of C. albicans GpiPs are published in the literature (12,16,21,55). In this review, we will not include the results of Paula Sundstrom's analysis since her work was done using assembly 6, an incomplete genome sequence.…”
Section: Candida Albicans Possesses 115 Putative Gpi-anchored Proteinsmentioning
confidence: 99%
“…In this review, we will not include the results of Paula Sundstrom's analysis since her work was done using assembly 6, an incomplete genome sequence. In an attempt to simplify our analysis, we have made a comprehensive list of putative GpiPs by combining the three data sets identified from assembly 19 (12,16,21). The three different teams presenting lists of C. albicans GpiPs identified different numbers of putative GpiPs (102, 104, and 169), but a careful analysis of each data set allowed us to refine our list (Table 1).…”
Section: Candida Albicans Possesses 115 Putative Gpi-anchored Proteinsmentioning
confidence: 99%